The Model of Policy and Regulation of Local Content Requirements in Indonesia - Muh Risnain (Faculty of Law, Universitas Padjadjaran, 2018)
Nowadays, many states apply policy on the Local Content Requirements (LCRs) as an instrument of international trade. The international trade law under the framework of World Trade Organization (WTO) actually requires equal treatment for both foreign and local business actors. However, the policy to apply LCRs based on national interest ignores the WTO’s principles. Since 2009, Indonesia is one of the states that apply LCRs based on national economic requirement and an argumentation that, currently, Indonesia has not become a party of GPA (Government Procurement Agreement). Therefore, Indonesia has no obligation to apply equal treatment principle in the procurement of government’s goods and service. The Indonesian government needs to construct LCRs regulation that can fulfill both international trade interests and national economic interests. Article 22 (3) of the Law Number 7 of 2014 on Trade mandates a Regulation of the Minister of Trade to set out the application of LCRs. Therefore, the Draft of the Regulation of the Minister of Trade on the use of domestic products is the most important legal requirement for current Indonesian trade. Therefore, this study suggests that the Minister of Home Affairs immediately should process the Regulation of the Minister of Trade as a Law on the use of domestic products. The results of the process can be a reference for government’s, as well as local governments’, agencies on the application of LCRs.Model Pengaturan Kewajiban Penggunaan Kandungan Lokal di IndonesiaAbstrakKebijakan negara-negara untuk memberlakukan LCRs dalam perdagangan internasional dewasa ini merupakan sebuah kenyataan yang dihadapi. Hukum perdagangan internasional dalam kerangka WTO sesungguhnya bertentangan dengan prinsip-prinsip utama WTO terutama prinsip national treatment yang menghendaki perlakuan yang sama antara pelaku usaha asing dan pelaku usaha dalam negeri. Namun demikian kebijakan yang memberlakukan LCRs berdasarkan pada prinsip kepentingan ekonomi nasional dapat saja mengabaikan prinsip-prinsip WTO. Indonesia sebagai salah satu negara yang menerapkan kebijakan LCRs sejak 2009 mendasarkan kebijakan pada kepentingan ekonomi nasional juga didasarkan pada argument bahwa hingga saat ini Indonesia belum menjadi pihak dalam GPA. Sehingga Indonesia dapa bebas dari kewajiban untuk menerapkan prinsip equal treatment dalam pengadaan barang dan jasa pemerintah. Model regulasi kebijakan LCRs di Indonesia yang dapat mengharmoniskan kepentingan perdagangan internasional dan kepentingan ekonomi nasional Indonesia adalah dengan segera mengatur peraturan khusus tentang LCRS. Pasal 22 (3) undang-undang Nomor 7 tahun 2014 tentang perdagangan mengamanatkan agar pemberlakuan LCRs diatur melalui Peraturan Menteri Perdagangan. Oleh karena itu, Rancangan Peraturan Menteri Perdagangan tentang penggunaan produk dalam negeri merupakan kebutuhan hukum terpenting yang saat ini dibutuhkan oleh dunia perdagangan Indonesia. Oleh karena itu, kajian ini menyarankan agar Menteri Dalam Negeri segera memproses Peraturan Menteri Perdagangan sebagai Undang-undang tentang penggunaan produk dalam negeri. Hasil dari proses tersebut dapat menjadi rujukan bagi lembaga pemerintah, maupun pemerintah daerah, tentang LCRs.DOI: https://doi.org/10.22304/pjih.v5n3.a10